Effect of Artificial Aging Test on PEEK CAD/CAM Fabricated Orthodontic Fixed Lingual Retainer - Ruwiaee, Riyadh A; Alhuwaizi, Akram F (Journal of Baghdad College of Dentistry, 2022)
Background: The purpose of this study was to evaluate the effect of in vitro long-term simulation of oral conditions on the bond strength of PEEK CAD/CAM lingual retainers.Material and methods: The sample consisted of 12 PEEK CAD/CAM retainers each composed of 2 centrally perforated 3x4mm pads joined by a connector. They were treated by 98% sulfuric acid for 1 minute and then conditioned with Single Bond Universal and bonded to the lingual surface of premolar teeth by 3M Transbond TM System. Half of the retainers were artificially aged using a 30-day water storage and 5000 thermocycling protocol before bond strength testing to compare with the non-aged specimens.Results: The artificially aged retainers showed a marginally lower bond strength than the non-aged retainers. However, independent sample t-test indicated that this difference was statistically not significant.Conclusion: The durability of the PEEK lingual retainer adhesive system has been confirmed using the well-known oral simulating artificial aging protocol of water storage and thermocycling.